Impact of Germination or Heat treatment of fenugreek seeds on some growth and blood characteristics in Awassi lambs. (NTU Journal of Agriculture and Veterinary Science, 2025)
The research was conducted on the field site of the College of Agriculture and Forestry at the University of Mosul on 20 Awassi lambs to find the effect on the blood properties and growth characteristics of Awassi lambs when using roasted, sprouted, and regular fenugreek. The average weight of the experiment animals was 25.7 ± 3.3 kg during the winter season, and the average age was 4-5 months )90 day period), The animals were divided into four groups.1st group represent the control. 2nd group the animals, 30 grams of dried fenugreek were added. 3rd group the animals, 30 grams of fenugreek It was exposed to heat. 4th group the animals, 30 grams of fenugreek were cultured for 48 hours and added to the feed of the fourth treatment. The research results indicated that there was no significant effect on the final weight, the rate of daily and total weight gain, and the carcass weights of Awassi lambs exposed to all types of fenugreek compared to the control, while a significant effect was found (P<0.05). Roasted fenugreek reduces sugar and triglycerides, sprouted fenugreek reduces cholesterol and triglycerides and raises total protein in blood serum, and urea raises protein and urea, while regular fenugreek helps reduce fat and thus has a positive effect on animals.